Organic-inorganic composite microsphere and preparation method thereof

By emulsifying using supergravity equipment in microsphere preparation, an S/O/W coated microsphere suspension emulsion is formed, which solves the problems of uneven particle size distribution and low production efficiency of microspheres in the prior art, and achieves high efficiency. Uniform microsphere preparation, suitable for medical beauty anti-aging injection fillers, has excellent biocompatibility and ability to stimulate collagen regeneration.

CN119318735AInactive Publication Date: 2025-01-17NINGBO CIBEI MEDICAL TREATMENT APPLIANCE

Patent Information

Application Number
CN202411858401.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-01-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing microsphere preparation process, the dispersed phase and the continuous phase solution are unevenly mixed, resulting in poor particle size distribution of microspheres, low production efficiency, easy blockage of channels, high energy consumption, and poor repeatability, making it difficult to meet the high efficiency and uniformity of the medical beauty market. Microsphere products demand.

Method used

Emulsification is carried out using supergravity equipment, and the microsphere suspension emulsion coated by surfactant is formed, and organic inorganic composite microspheres are prepared by separation and freeze-drying to achieve uniform concentration of particle size distribution, suitable for regeneration Anti-aging injection filler.

Benefits of technology

It achieves the uniformity of microsphere particle size distribution and production efficiency, reduces production costs, avoids pollution and quality fluctuations, and provides good biocompatibility and anti-aging effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318735A_ABST
    Figure CN119318735A_ABST
Patent Text Reader

Abstract

The invention relates to an organic-inorganic composite microsphere and a preparation method thereof, and is characterized in that an amphiphilic polylactic acid organic material and inorganic particles are adopted, emulsification is carried out through a surfactant and supergravity equipment to form an S / O / W coated microsphere suspension emulsion, and then separation and freeze drying are carried out to obtain the organic-inorganic composite microsphere. The prepared organic-inorganic composite microsphere material is rich in various active components, can stimulate regeneration of tissue collagen in a more diversified manner as a component of a regenerative injection anti-aging filler, adopts a method for preparing microspheres through supergravity emulsification, and enhances a liquid-liquid heterogeneous micro-mixing process in a supergravity environment, so that the regeneration of the tissue collagen can be promoted, and the regeneration of the tissue collagen can be promoted. The prepared composite microsphere product is better in quality, the particle size distribution of the microspheres is more uniform and concentrated, the size of the microspheres is adjustable in a wide particle size range of 100nm-200mu m, and the method can realize continuous production, is good in stability and is easy to amplify.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the fields of regenerative injection filling medical aesthetics and polymer microsphere preparation technology, and more specifically to an organic-inorganic composite microsphere, a preparation method thereof, and an application thereof. Background Art

[0002] With the rapid growth of my country's light medical beauty market, injectable filling medical beauty products have evolved from traditional hyaluronic acid and collagen to the renewable stage of "polylactic acid-based microspheres + N". Amphiphilic polylactic acid materials such as PLGA, PEG-PLGA, and PEG-PLLA introduce hydrophilic groups through graft copolymerization with polylactic acid, which well achieves the dispersion of microspheres in sodium hyaluronate gel and will not aggregate into lumps after injection into the human body. In order to better meet the rapidly growing demand for minimally invasive medical beauty among the beauty-loving group, and to stimulate the regeneration of human collagen in a long-term manner. It is necessary to explore the addition of multiple active components with good biocompatibility and anti-aging properties on the basis of existing injectable filling products.

[0003] Zinc and magnesium ions contained in inorganic mineral materials such as zinc oxide, magnesium oxide, and magnesium carbonate have a good regulatory effect on the human microenvironment. Composite microsphere materials with polylactic acid-based microspheres as drug carriers coated with the above inorganic components have been widely proven to have good biocompatibility and optimized osteogenesis. Similarly, composite microsphere materials prepared by doping amphiphilic polylactic acid materials with inorganic particles such as zinc oxide, magnesium oxide, and magnesium carbonate have broad application prospects in the field of stimulating human collagen regeneration and anti-aging.

[0004] In the preparation of polymer microspheres, the commonly used technical routes include emulsion solvent evaporation, spray drying, solvent phase separation, microfluidics, membrane emulsification and other methods. Among them, the emulsification method is simple to operate and the easiest to scale up, and it is also the most commonly used method in industrial-scale production. This method is to mix the water-oil two-phase solution through mechanical stirring or high-pressure homogenization to obtain the required type of emulsion such as water-in-oil (O / W), water-in-oil-in-solid (S / O / W), etc., and then remove the solvent and solidify it to obtain polymer microspheres.

[0005] The emulsification equipment and processes commonly used in the market, such as high-speed flow shearing machines, stirring kettles, and high-pressure homogenizers, have the following problems: The uneven mixing between the dispersed phase and the continuous phase solution results in a wide distribution of particle size of the internal phase droplets and a poor particle size distribution of the microspheres obtained after solidification.

[0006] The intermittent operation production mode of the stirred tank has poor repeatability between different batches and the quality of the microsphere products fluctuates significantly.

[0007] High-pressure homogenization and emulsification equipment has low production efficiency, easy channel clogging and high energy consumption.

[0008] The current microsphere preparation process still faces certain challenges in terms of microsphere product quality, namely microsphere particle size distribution and production efficiency. Summary of the invention

[0009] The purpose of the present invention is to solve the deficiencies of the above-mentioned technologies and to provide an organic-inorganic composite microsphere having multiple active components with good biocompatibility and anti-aging properties, and having a more uniform and concentrated particle size distribution of the microspheres and a preparation method thereof.

[0010] In order to achieve the above-mentioned purpose, the present invention provides an organic-inorganic composite microsphere, which is characterized by using amphiphilic polylactic acid organic material and inorganic particles, emulsifying through surfactants and using supergravity equipment to form S / O / W coated microsphere suspension emulsion, and then separating and freeze-drying to obtain the organic-inorganic composite microsphere; the amphiphilic polylactic acid organic material includes polylactic acid-glycolic acid copolymer (PLGA), polylactic acid-glycolic acid polyethylene glycol copolymer (PEG-PLGA), poly-L-lactic acid-polyethylene glycol block copolymer (PEG-PLLA), PLLA; the surfactant includes one or more of polyvinyl alcohol, glycerol, Tween-80, Span-80; the inorganic particles include one or more of zinc oxide, magnesium oxide, magnesium carbonate and magnesium hydroxide; the mass ratio of the amphiphilic polylactic acid organic material and the inorganic particles to the amphiphilic polylactic acid organic material is 1:200 to 1:5.

[0011] The present invention provides a method for preparing organic-inorganic composite microspheres, which is characterized by comprising the following steps: S1. Add a certain amount of surfactant into injectable water and stir to dissolve to prepare an aqueous phase solution; add amphiphilic polylactic acid material and inorganic particles into an oil phase solvent to prepare an oil phase solution; the water-oil two-phase solution maintains a certain phase ratio; S2. Set the speed of the supergravity equipment to 300-3000 r / min, and pass a certain amount of water-oil two-phase solution from the corresponding liquid inlet into the supergravity equipment through a pump, perform shear emulsification at room temperature, and collect the S / O / W emulsion from the liquid outlet at the bottom of the supergravity equipment; S3, mechanically stirring the S / O / W emulsion obtained in step S2 at a speed of 200 to 1000 r / min for 6 to 12 hours at room temperature, centrifuging and washing the microsphere suspension for 3 to 5 times, and then freeze-drying, thereby obtaining organic-inorganic composite microspheres in the range of 100 nm to 200 μm; The oil phase solvent includes one or more of dichloromethane, chloroform and ethyl acetate; In step S1, the surfactant concentration of the aqueous solution is 5 to 100 mg / ml; In step S1, the amphiphilic polylactic acid material, in PLLA-PEG, the molecular weight of PLLA is 80,000-240,000, and the molecular weight of PEG is 700-6,000; in PLGA or PLGA-PEG, LA / GA in PLGA is 90 / 10, the molecular weight is 80,000-240,000, and the molecular weight of PEG is 700-6,000; the concentration of the amphiphilic polylactic acid material in the oil phase is 20-200 mg / ml; In step S1, the concentration of inorganic particles in the oil phase is 0.1 to 40 mg / ml; In step S1, the ratio of the water-oil two-phase solution is 1:1 to 20:1.

[0012] The water-oil two-phase feed rate can be 300-1500 ml / min.

[0013] The supergravity equipment is selected from one of baffled supergravity equipment, spiral channel supergravity equipment, stator-rotor supergravity equipment, rotating disc supergravity equipment, rotating packed bed supergravity equipment, external circulation equipment or internal circulation equipment.

[0014] The organic-inorganic composite microspheres provided by the present invention can be used as a component of a regenerative anti-aging injection filler, combined with a cross-linked sodium hyaluronate gel and sterilized, mixed, and filled for medical beauty injection; the cross-linked sodium hyaluronate gel can be replaced by animal collagen, human collagen, CMC cellulose, chitosan, amino acids or sodium alginate; the cross-linking agent types include but are not limited to BDDE (1,4-butanedialdehyde), DVS (dienyl disiloxane), PEGDE (polyethylene glycol diglycidyl ether) and lysine.

[0015] The organic-inorganic composite microsphere material prepared by the present invention is rich in a variety of active components. As a component of the regenerative injectable anti-aging filler, it can stimulate the regeneration of collagen in human tissue in a more diversified way, promote the ability of cell proliferation and differentiation, accelerate tissue repair and regeneration; affect the synthesis and secretion of collagen, and stimulate the regeneration of collagen. The present invention adopts a method for preparing microspheres by ultra-gravity emulsification. By strengthening the liquid-liquid heterogeneous micro-mixing process under an ultra-gravity environment, the particle size distribution of the microsphere product is more uniform and concentrated, and the size of the microsphere is adjustable within a wide particle size range of 100nm to 200μm. This method can realize continuous production, has good stability, and is easy to scale up. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The flow chart for the preparation of organic-inorganic composite microspheres; Figure 2 The SEM and particle size distribution diagram of PEG-PLLA@ZnO microspheres prepared in Example 1; Figure 3This is the mapping diagram of PEG-PLLA@ZnO microspheres prepared in Example 1; Figure 4 The SEM and particle size distribution diagram of the PLLA@MgO composite microspheres prepared in Example 2; Figure 5 This is the mapping diagram of the PLLA@MgO composite microspheres prepared in Example 2; Figure 6 The SEM and particle size distribution diagram of the PLGA@ZnO / MgO / MgCO3 composite microspheres prepared in Example 3; Figure 7 This is the mapping diagram of PLGA@ZnO / MgO / MgCO3 composite microspheres prepared in Example 3. DETAILED DESCRIPTION

[0017] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0018] Example 1

[0019] The present embodiment provides an organic-inorganic composite microsphere, which uses an amphiphilic polylactic acid organic material and inorganic particles, is emulsified by a surfactant and ultra-gravity equipment to form an S / O / W-coated microsphere suspension emulsion, and then separated and freeze-dried to obtain an organic-inorganic composite microsphere; in this embodiment, the amphiphilic polylactic acid organic material is poly-L-lactic acid-polyethylene glycol block copolymer (PEG-PLLA); the surfactant is polyvinyl alcohol; and the inorganic particles are zinc oxide particles; The specific preparation method is to add 1.5g of polyvinyl alcohol to 150ml of deionized water, heat and stir at 80°C for 1h, and naturally cool to room temperature to obtain an aqueous phase solution; add 0.6g of PEG-PLLA with a molecular weight of 150,000 and 0.012g of zinc oxide particles with a particle size of 20nm into 30ml of dichloromethane and dissolve them to obtain an oil phase solution.

[0020] The speed of the supergravity equipment was set to 900r / min through the frequency regulator, and the water-oil two-phase solution was introduced into the liquid inlet through the pump respectively. The water phase feeding rate was set to 1200ml / min and the oil phase feeding rate was set to 240ml / min. The motor and the pump were turned on to realize the feeding and supergravity emulsification of the water-oil two-phase solution, and the S / O / W emulsion was collected from the liquid outlet at the bottom of the supergravity equipment.

[0021] At room temperature, the emulsion after ultragravity emulsification was mechanically stirred at 400r / min for 10h to remove the dichloromethane solvent; the microsphere suspension after desolventization and solidification was centrifuged and washed at a centrifugal speed of 5000r / min, 30ml of deionized water was used for each washing, and the PEG-PLLA@ZnO composite microspheres were obtained by freeze drying. The particle size distribution of the prepared PEG-PLLA@ZnO composite microspheres is D10: 18.47μm, D50: 26.53μm, D90: 36.75μm, Span: 0.6890 (such as Figure 2 , Figure 3 as shown).

[0022] The composite microsphere product prepared by the ultra-gravity emulsification process described in this embodiment has a narrow particle size distribution. It meets the current medical beauty market's demand for the particle size of microsphere products, can save the microsphere screening post-processing stage, reduce production costs, and improve production efficiency. The one-step preparation process with a shorter process flow avoids pollution in the production process and ensures the safety of medical beauty microsphere products.

[0023] The PEG-PLLA@ZnO composite microspheres obtained in this example are used as a component of the regenerative injectable anti-aging filler, combined with the cross-linked sodium hyaluronate gel, sterilized, mixed, and filled for medical beauty injection. The biological performance evaluation fully demonstrates safety and effectiveness, and has a good cosmetic effect.

[0024] In vitro cell and mouse subcutaneous injection biological performance evaluation experiments were carried out, with cross-linked sodium hyaluronate gel containing PEG-PLLA@ZnO composite microspheres (PEG-PLLA@ZnO / HA) and cross-linked sodium hyaluronate gel containing PEG-PLLA microspheres (PEG-PLLA / HA) as the experimental group and blank cross-linked sodium hyaluronate gel (HA) as the control group.

[0025] The pH value of PEG-PLLA@ZnO / HA is maintained in the weak alkaline range of 7.01~7.5, which is beneficial to neutralize the lactic acid generated during the degradation process of polylactic acid materials and avoid tissue acidification-induced inflammatory response.

[0026] The results showed that PEG-PLLA@ZnO / HA, PEG-PLLA / HA and HA had no cytotoxicity. Compared with HA and PEG-PLLA / HA, the largest number of cells was observed in PEG-PLLA@ZnO / HA, and PEG-PLLA@ZnO / HA enhanced cell activity. The expression of inflammation-related genes in PEG-PLLA / HA increased compared with the HA control group, while the expression of inflammation-related genes in PEG-PLLA@ZnO / HA was significantly reduced, which was due to the neutralization of the acidic intermediates of polylactic acid biodegradation by Zn ions released during the degradation of PEG-PLLA@ZnO microspheres.

[0027] After subcutaneous injection of PEG-PLLA@ZnO / HA, PEG-PLLA / HA, and HA in mice, soft tissues were evaluated at 4, 8, and 16 weeks. PEG-PLLA@ZnO / HA, PEG-PLLA / HA, and HA showed no abnormal morphological changes and showed good tolerance, without acute inflammation, abscess formation, or tissue necrosis near the implantation site. In addition, there was no obvious tissue reactivity or cell migration away from the implantation site.

[0028] Compared with HA and PEG-PLLA / HA, the increased number of blood vessels and thickened collagen wall were more obviously observed in PEG-PLLA@ZnO / HA. The expression levels of collagen biosynthesis-related genes in HA, PEG-PLLA / HA and PEG-PLLA@ZnO / HA were gradually upregulated. Skin is mainly composed of type I collagen. In-depth evaluation of collagen biosynthesis-related protein marker COL1A1 showed that the expression of collagen markers was upregulated in PEG-PLLA@ZnO / HA compared with HA and PEG-PLLA / HA.

[0029] The biological performance evaluation results prove that the PEG-PLLA@ZnO composite microspheres provided by the present invention have excellent biocompatibility and can more efficiently stimulate tissue collagen regeneration.

[0030] Example 2

[0031] The organic-inorganic composite microspheres provided in this embodiment are made of amphiphilic polylactic acid organic material and inorganic particles, which are emulsified by surfactants and ultra-gravity equipment to form S / O / W coated microsphere suspension emulsions, and then separated and freeze-dried to obtain organic-inorganic composite microspheres; in this embodiment, the amphiphilic polylactic acid organic material is PLLA with a molecular weight of 110,000; the surfactant is polyvinyl alcohol; and the inorganic particles are magnesium oxide particles with a particle size of 50 nm; The specific preparation method is as follows: 1.7 g of polyvinyl alcohol is added to 170 ml of deionized water, heated and stirred at 80°C for 1 hour, naturally cooled to room temperature, 30 ml of glycerol solution is added to the polyvinyl alcohol aqueous solution and stirred to dissolve to obtain an aqueous phase solution; 0.08 g of magnesium oxide particles with a particle size of 50 nm and 0.8 g of PLLA with a molecular weight of 110,000 are added to 20 ml of dichloromethane and dissolved to obtain an oil phase solution.

[0032] The speed of the supergravity equipment was set to 1000r / min through the frequency regulator, and the water-oil two-phase solution was introduced into the liquid inlet through the pump, and the feeding speed of the water phase solution was set to 1200ml / min and the feeding speed of the oil phase solution was set to 120ml / min. The motor and pump were turned on to realize the feeding and supergravity emulsification of the water-oil two-phase solution, and the primary emulsion was collected from the liquid outlet at the bottom of the supergravity equipment.

[0033] The primary emulsion was fed into an ultra-gravity device with a rotation speed of 1000 r / min via a peristaltic pump at a feed rate of 600 ml / min for a second emulsification, and the product emulsion was collected from the liquid outlet.

[0034] The ultra-gravity emulsion was mechanically stirred at room temperature and 400 r / min for 10 h to remove the dichloromethane solvent. The microsphere suspension after desolventization and solidification was centrifuged and washed at a centrifugal speed of 5000 r / min, 30 ml of deionized water was used for each washing, and the centrifugal washing was performed 3 times. The PLLA@MgO composite microspheres were obtained by freeze-drying.

[0035] The particle size distribution of the prepared PLLA@MgO composite microspheres is D10: 21.13μm, D50: 41.98μm, D90: 67.56μm, Span: 1.1060 (such as Figure 4 , Figure 5 as shown).

[0036] The PLLA@MgO composite microspheres obtained in this example are used as a component of a regenerative injectable anti-aging filler, combined with a cross-linked sodium hyaluronate gel, sterilized, mixed, and filled for medical beauty injection. The various biological performance evaluation tests described in Example 1 were also performed, and the biological performance evaluation results proved that the PLLA@MgO composite microspheres provided by the present invention have excellent biocompatibility and can more efficiently stimulate tissue collagen regeneration.

[0037] Example 3

[0038] The organic-inorganic composite microspheres provided in this embodiment are made of amphiphilic polylactic acid organic material and inorganic particles, which are emulsified by surfactant and ultra-gravity equipment to form S / O / W coated microsphere suspension emulsion, and then separated and freeze-dried to obtain organic-inorganic composite microspheres; in this embodiment, the amphiphilic polylactic acid organic material is PLGA with a molecular weight of 120,000 and LA / GA=75:25; the surfactant is polyvinyl alcohol; the inorganic particles are 2mg / ml concentration of zinc oxide and magnesium oxide / magnesium carbonate mixed nanoparticles with a mass ratio of 1:1; The specific preparation method is as follows: polyvinyl alcohol weighed at a concentration of 50 mg / ml is added to deionized water, heated and stirred at 80°C for 1 hour, and naturally cooled to room temperature to obtain an aqueous solution; PLGA with a molecular weight of 120,000 and LA / GA=75:25 is weighed at a concentration of 10 mg / ml and zinc oxide and magnesium oxide / magnesium carbonate mixed nanoparticles with a mass ratio of 1:1 are weighed at a concentration of 2 mg / ml, added to ethyl acetate and dissolved to obtain an oil phase solution; the ratio of the water-oil phase solution is 1:1.

[0039] Adjust the circulating water temperature of the jacket of the supergravity equipment to 6°C, set the speed of the supergravity equipment to 2500r / min, and feed the water-oil two-phase solution into the liquid inlet through the pump, respectively, and set the feeding speed to 400ml / min. Turn on the motor and pump to realize the feeding and supergravity emulsification of the water-oil two-phase solution, and collect the S / O / W emulsion from the liquid outlet at the bottom of the supergravity equipment.

[0040] The ultra-gravity emulsion was mechanically stirred at room temperature and 700 r / min for 5 h to remove the ethyl acetate solvent. The microsphere suspension after desolventization and solidification was centrifuged and washed at a centrifugal speed of 5000 r / min, 30 ml of deionized water was used for each washing, and the centrifugal washing was performed 3 times, and the PLGA@ZnO / MgO / MgCO3 composite microspheres were obtained by freeze drying.

[0041] The particle size of the prepared PLGA@ZnO / MgO / MgCO3 composite microspheres is D10: 32.14μm, D50: 51.81μm, D90: 74.23μm, Span: 0.8125 (such as Figure 6 , Figure 7 as shown).

[0042] The PLGA@ZnO / MgO / MgCO3 composite microspheres obtained in this example are used as a component of a regenerative injectable anti-aging filler, combined with a cross-linked sodium hyaluronate gel and sterilized, mixed, and filled for medical beauty injections. The various biological performance evaluation tests described in Example 1 are also carried out. The biological performance evaluation results demonstrate that the PLGA@ZnO / MgO / MgCO3 composite microspheres provided by the present invention have superior biocompatibility and can more efficiently stimulate tissue collagen regeneration.

[0043] It can be seen from the above examples that the ultra-gravity emulsification optimization process in Examples 1 to 3 achieves uniform and controllable preparation of polylactic acid-based microspheres. The particle size distribution of the prepared polylactic acid-based microspheres is concentrated and the span is small. Inorganic particles such as zinc oxide, magnesium oxide, and magnesium carbonate are added to the oil phase solution at a certain concentration under the ultra-gravity emulsification optimization process. The PEG-PLLA@ZnO, PLLA@MgO, and PLGA@ZnO / MgO / MgCO3 organic-inorganic composite microspheres prepared by the S / O / W emulsification method have a better particle size distribution.

[0044] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.

[0045] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An organic-inorganic composite microsphere, characterized in that The method adopts amphiphilic polylactic acid organic material and inorganic particles, and uses surfactants and supergravity equipment to emulsify them to form S / O / W coated microsphere suspension emulsion, and then separates and freeze-dries them to obtain organic-inorganic composite microspheres; the amphiphilic polylactic acid organic material includes polylactic acid-glycolic acid copolymer, polylactic acid-glycolic acid polyethylene glycol copolymer, poly-L-lactic acid-polyethylene glycol block copolymer, and PLLA; the surfactant includes one or more of polyvinyl alcohol, glycerol, Tween-80, and Span-80; the inorganic particles include one or more of zinc oxide, magnesium oxide, magnesium carbonate, and magnesium hydroxide; the mass ratio of the amphiphilic polylactic acid organic material and the inorganic particles to the amphiphilic polylactic acid organic material is 1:200 to 1:

5.

2. The method for preparing an organic-inorganic composite microsphere according to claim 1, characterized in that The following steps are involved: S1. Add a determined amount of surfactant into injectable water and stir to dissolve to prepare an aqueous solution; The amphiphilic polylactic acid material and inorganic particles are added into the oil phase solvent to prepare the oil phase solution; the water-oil two-phase solution maintains a certain phase ratio; S2. Set the speed of the supergravity equipment to 300-3000 r / min, and pass a certain amount of water-oil two-phase solution from the corresponding liquid inlet into the supergravity equipment through a pump, perform shear emulsification at room temperature, and collect the S / O / W emulsion from the liquid outlet at the bottom of the supergravity equipment; S3, mechanically stirring the S / O / W emulsion obtained in step S2 at a speed of 200 to 1000 r / min for 6 to 12 hours at room temperature, centrifuging and washing the microsphere suspension for 3 to 5 times, and then freeze-drying, thereby obtaining organic-inorganic composite microspheres in the range of 100 nm to 200 μm; The oil phase solvent includes one or more of dichloromethane, chloroform and ethyl acetate; In step S1, the surfactant concentration of the aqueous solution is 5 to 100 mg / ml; In step S1, the amphiphilic polylactic acid material, in PLLA-PEG, the molecular weight of PLLA is 80,000-240,000, and the molecular weight of PEG is 700-6,000; in PLGA or PLGA-PEG, LA / GA in PLGA is 90 / 10, the molecular weight is 80,000-240,000, and the molecular weight of PEG is 700-6,000; the concentration of the amphiphilic polylactic acid material in the oil phase is 20-200 mg / ml; In step S1, the concentration of inorganic particles in the oil phase is 0.1 to 40 mg / ml; In step S1, the ratio of the water-oil two-phase solution is 1:1 to 20:

1.

3. The method for preparing organic-inorganic composite microspheres according to claim 2, characterized in that The supergravity equipment is selected from one of baffled supergravity equipment, spiral channel supergravity equipment, stator-rotor supergravity equipment, rotating disc supergravity equipment, rotating packed bed supergravity equipment, external circulation equipment or internal circulation equipment.

4. The use of an organic-inorganic composite microsphere according to claim 1, characterized in that As a component of regenerative anti-aging injectable fillers, it is combined with cross-linked sodium hyaluronate gel and sterilized, mixed, and filled for medical beauty injections; the cross-linked sodium hyaluronate gel can be replaced by animal collagen, human collagen, CMC cellulose, chitosan, amino acids or sodium alginate; cross-linking agent types include BDDE, DVS, PEGDE and lysine.

Citation Information

Patent Citations

  • Method for adjusting polymer micelle particle size by using hypergravity technique

    CN104151568A

  • Injectable bone repair material with controllable magnesium ion release behavior and preparation method of material

    CN108283729A

  • Supergravity preparation method of W / O / W type multiple emulsion

    CN111939779A

  • Preparation method of uniform polymer microspheres

    CN114099448A

  • Method for preparing self-assembled microcapsule

    CN114653314A

Cited By

  • Preparation method of composite microspheres for medical beauty injection filler

    CN120267901A